The Quest for Subsidies Reforms in the Middle East and North Africa Region : A Microsimulation Approach to Policy Making - Verme, Paolo (Cham, Switzerland: Springer, 2017)
The objective of this book is to capitalize on the work undertaken by the World Bank in the MENA Region between 2010 and 2014 using a particular model specifically designed for the distributional analysis of subsidies and the simulation of subsidies reforms. The model is called “SUBSIM” and has been used uniformly in all the seven countries where the World Bank operated. The focus of the book is the distribution of subsidies and the simulation of subsidy reforms in a partial equilibrium framework. The distributional analysis of subsidies provides information on who benefits from existing subsidies, and the simulations of subsidy reforms provide information on the outcomes of the reforms in terms of government budget, household welfare, poverty, inequality, and the trade-offs between these outcomes. It is a partial equilibrium approach in that we focus on the final consumption market only. The book covers energy and food subsidies. The countries covered are Djibouti, the Arab Republic of Egypt, the Islamic Republic of Iran, Jordan, Libya, Morocco, Tunisia, and the Republic of Yemen.